Antidiarrheal activity of methanolic leaf extract of Rumex vesicarius (Bangladesh Journal of Pharmacology, 2016)
This study evaluates the antidiarrheal activity of Rumex vesicarius (leaf) by using in vitro and in vivo assays. Antidiarrheal effect of R. vesicarius was  evaluated using castor oil-induced diarrhea model in rat. Weight and  volume of the intestinal content were assessed using the enteropooling method. Atropine (3 mg/kg, i.p) was used as positive control. R. Vesicarius at the  doses of 200 and 400 mg/kg p.o. significantly retarded castor oil-induced  enteropooling and intestinal transit. The gastrointestinal transit rate was  studied and R. vesicarius at the doses of 200 and 400 mg/kg significantly inhibited (p